Reducing the Formaldehyde Levels in Meatballs using Fruit of Averrhoa bilimbi (Belimbing Wuluh) - Gilang Robi Sadino; Fath Dwisari; Puspa Amalia; Abdurraafi’ Maududi Dermawan (Universitas Airlangga, 2026)
Meatballs (Bakso) are processed meat products that are widely consumed in Indonesia. Owing to their high moisture and protein content, meatballs are highly susceptible to microbial spoilage, leading some vendors to illegally use formaldehyde as a preservative to extend shelf life. Prolonged consumption of formaldehyde-contaminated foods may pose serious health risks. Therefore, this study aimed to evaluate the effectiveness of Averrhoa bilimbi (belimbing wuluh) juice in reducing formaldehyde levels in meatballs and to determine the most effective juice concentration. A randomized pretest–posttest experimental design was employed using 12 commercial beef meatball samples collected from a local market in Pontianak and spiked with formaldehyde under laboratory conditions. The samples were treated with 30, 40, and 50% A. bilimbi juice for 60 min. Formaldehyde concentrations were quantified and validated using UV-Vis spectrophotometry. The results demonstrated a significant reduction in formaldehyde levels after juice application. The reductions achieved with 30%, 40%, and 50% juice were 27.07%, 28.78%, and 65.80%, respectively. In conclusion, formaldehyde reduction increased with increasing juice concentration, with the 50% treatment producing the greatest reduction (65.80%). Further studies using naturally contaminated food samples are required to verify the effectiveness and practical applicability of this approach. Keywords: Averrhoa bilimbi, Belimbing Wuluh, formaldehyde, meatball, Spectrofotometry UV-Vis